2009
DOI: 10.1105/tpc.108.065052
|View full text |Cite
|
Sign up to set email alerts
|

Statolith Sedimentation Kinetics and Force Transduction to the Cortical Endoplasmic Reticulum in Gravity-SensingArabidopsisColumella Cells  

Abstract: The starch statolith hypothesis of gravity sensing in plants postulates that the sedimentation of statoliths in specialized statocytes (columella cells) provides the means for converting the gravitational potential energy into a biochemical signal. We have analyzed the sedimentation kinetics of statoliths in the central S2 columella cells of Arabidopsis thaliana. The statoliths can form compact aggregates with gap sizes between statoliths approaching <30 nm. Significant intra-aggregate sliding motions of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
147
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 81 publications
4
147
0
Order By: Relevance
“…statocytes. 40 Although flax and Arabidopsis may have similar sedimentation kinetics, the saturation of the graviresponse after 10 min is also supported by our observation of maximal curvature after 10 min reorientation. Investigations with excess starch mutants indicate that gravisensing is not saturated 41 and studies of the presentation time show that much shorter reorientation times than signal saturation are sufficient to induce curvature and suggest that amyloplast sedimentation is not necessary for the initiation of gravitropism.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…statocytes. 40 Although flax and Arabidopsis may have similar sedimentation kinetics, the saturation of the graviresponse after 10 min is also supported by our observation of maximal curvature after 10 min reorientation. Investigations with excess starch mutants indicate that gravisensing is not saturated 41 and studies of the presentation time show that much shorter reorientation times than signal saturation are sufficient to induce curvature and suggest that amyloplast sedimentation is not necessary for the initiation of gravitropism.…”
Section: Discussionsupporting
confidence: 68%
“…Investigations with excess starch mutants indicate that gravisensing is not saturated 41 and studies of the presentation time show that much shorter reorientation times than signal saturation are sufficient to induce curvature and suggest that amyloplast sedimentation is not necessary for the initiation of gravitropism. 40 While earlier studies focused on the detection limit (presentation time) that is sufficient to induce curvature, 28,35 this study demonstrates saturation of the gravity stimulus likely coincides with the amyloplast sedimentation. Studies on gravity-induced gene expression, hormone redistribution and signal transduction should use this time as reference point for maximal effects of a (single) acceleration or reorientation stimulus.…”
Section: Discussionmentioning
confidence: 98%
“…This result may represent the angle statoliths move within columella cells at the midpoint of a root gravitropic response (33). Live imaging revealed that the initial 908 gravity stimulus causes statoliths to be displaced from the rootward (apical) end of columella cells to the new lower cell wall (26). However, at a root angle of ∼408 statoliths return to the rootward face of columella cells (Fig.…”
Section: Lateral Auxin Gradient Forms Transiently and Dissipates Aftementioning
confidence: 94%
“…Specialized starch-filled organelles termed statoliths move within 5 min of a gravity stimulus in gravity-sensing columella cells (26,27). It has been proposed that statolith sedimentation onto the lower side of these cells triggers the formation of the lateral auxin gradient (28,29).…”
Section: Gravity-induced Lateral Auxin Gradient Is Dependent On Statomentioning
confidence: 99%
“…5,6 The physical signal of statolith sedimentation is converted to physiological information by a mechanism still to be fully deciphered, and transmitted to the root elongation zone located at a distance from the root cap. Several constituents of this physiological response have been identified including changes in pH, reactive oxygen species, Ca +2 induced signaling, and modulation of auxin transport.…”
mentioning
confidence: 99%